Match performance profiles of goalkeepers of elite football teams - Hongyou L.; Gomez, M. A.; Lago-Penas, C.; Arias-Estero, J.; Stefani, R. (International Journal of Sports Science and Coaching, 2015)
The aim of the current study was to examine match performance of elite goalkeepers considering three situational variables (opposition, outcome and location). Match performance statistics of 46 goalkeepers who played 744 full matches during season 2012-13 in the Spanish First Division Professional Football League were analyzed. Results indicated that there were only three performance indicators (Fouls Drawn, Fouls Committed and Tackles) that showed no differences among goalkeepers of high, intermediate and low levels of team. The sole indicator was Saves which differed for goalkeepers of all three team levels and also the sole varied indicator for goalkeepers of intermediate and low level teams when facing different opponent levels. High level team goalkeepers showed differences in none of their match performance indicators during matches won, drawn and lost. However, Saves (F2,244=6.459, p<0.01, p²=0.05) was the sole indicator which differed for low level team goalkeepers when the final outcome is different. Different variations in performance indicators were found depending on the match location for different team levels. The most interesting performance differential was that a goalkeeper of a high-level team had a higher number of Saves when playing against a low-level team than a high-level team or an intermediate-level team. Information provided by the profiles can be used by coaches to modify training programs depending on the game context of upcoming matches. Results can also enable a more thorough understanding of goalkeeper's performance profiles from different team levels, thus can be used for talent identification and player selection in the transfer market. ABSTRACT FROM AUTHOR